BVR: a Storage Format for Navigation in Volumetric Data - Zúñiga, Leonardo; Hidrobo, Francisco (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we present the design and implementation of a format for volumetric data storage, along with the corresponding resolution algorithms of requests. This format allows the implantation of rendering algorithms with capacities to respond fast and efficiently to navigation requests with arbitrary trajectories. The proposal is based on grouping of voxel data in blocks (clusters) which match with the disk blocks size. Beside, we propose a multilayer model and develop a library that allows the usage of our format. The proposed model can be used in the visualization of huge volumetric data and its usefulness can be improved to support navigation based on data properties. To evaluate our proposal, we developed a visualization application which tests stability and performance of the implemented library and shows like using it.